Synthesis and Characterization of High‐Entropy CrMoNbTaVW Thin Films Using High‐Throughput Methods. Issue 2 (15th September 2022) - Schweidler, Simon; Schopmans, Henrik; Reiser, Patrick; Boltynjuk, Evgeniy; Olaya, Jhon Jairo; Singaraju, Surya Abhishek; Fischer, Franz; Hahn, Horst; Friederich, Pascal; Velasco, Leonardo
Abstract : High‐entropy alloys (HEAs) or complex concentrated alloys (CCAs) offer a huge research area for new material compositions and potential applications. Since the combination of several elements sometimes leads to unexpected and unpredictable material properties. In addition to the element combinations, the optimization of the element proportions in CCAs and HEAs is also a decisive factor in tailoring desired material properties. However, it is almost impossible to achieve the composition and characterization of CCAs and HEAs with a sufficient number of compositions by conventional experiments. Therefore, an optimized high‐throughput magnetron sputtering synthesis to fabricate a new HEA gradient layer of six elements is presented. With this approach, the compositional space of the HEA system CrMoNbTaVW can be studied in different subsections to determine the influence of the individual elements and their combinations on the structure, morphology, and physical properties (hardness and resistivity). It is found that the Cr‐, Ta‐, and W‐rich phases, which have a grain size of 10–11 nm, exhibit the hardest mechanical properties, whereas V‐, Ta‐, and Cr‐rich compounds exhibit the highest electrical resistivity. The combination of high‐throughput synthesis, automated analysis tools, and automated data interpretation enables rapid and time‐efficient characterization of the novel CrMoNbTaVW gradient film. Abstract : Herein, a time‐efficient investigation of complex‐concentration CrMoNbTaVW alloys is presented. High‐throughput synthesis and automated characterization and analysis techniques provide a large dataset that can be used to create data libraries for complex material systems.